Pola Mata Pencaharian Masyarakat Pesisir di Desa Siwar Kabupaten Buru Selatan - Soulisa, Senen; Tawainella, M. Nour; Subair, Subair (Lembaga Intelektual Muda (LIM) Maluku, 2023)
Coastal areas as a transitional area between land and sea which are potential resources in Indonesia. Livelihoods are traditionally carried out by both farmers and fishermen. The lack of government attention in empowering local communities is one of the factors in the lack of development of the village. This has resulted in the problem of poverty is a problem that has needed attention, especially by the local government. The type of research used is descriptive qualitative, namely research that aims to describe in detail certain social phenomena. The subjects in this study were determined purposively. The instruments used are observation and interviews. The data analysis used is qualitative data analysis consisting of data reduction, data presentation, and conclusions. The results of the data analysis found that the livelihood pattern of the people of Siwar village was originally as fishermen. However, due to economic factors, namely the demand for the needs of life on land, began to change from the fishery sector as a fisherman to a clove and nutmeg farmer. As a result of changes in livelihood, it naturally has an impact on the welfare of the people of Siwar village itself, namely an increase in the number of college graduates and an increase in the housing sector